Republic of Botswana : Accounting and Auditing - World Bank (Washington, DC, 2012)
This accounting and auditing report, part of the Observance of Standards and Codes (ROSC) for the Republic of Botswana, provides an assessment of accounting and auditing practices within the corporate sector in Botswana with reference to the International Financial Reporting Standards issued by the International Accounting Standards Board, and International Standards on Auditing issued by the International Federation of Accountants. Botswana has made considerable efforts in aligning its accounting and auditing practices with internationally accepted standards and codes. Corporate accounting and disclosure practices have considerably improved over the last 5 years. Monitoring and enforcement of financial reporting requirements in the banking sector have contributed to improved transparency of the financial sector. Even with progress, there is room for further improvements. The report highlights areas that need attention for strengthening the infrastructure of accounting and auditing practices in Botswana. The report concludes with recommendations to integrate with regional and sub-regional initiatives, wherever applicable, to share resources in order to strengthen accounting and auditing practices in Botswana.